The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ol.2017.6852
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian sterile 20‑like kinase 1 expression and its prognostic significance in patients with breast cancer

Abstract: Mammalian sterile 20-like kinase 1 (Mst1) is a major inhibitor of cell proliferation, and is involved in apoptosis, oncogenesis and organ growth via its ubiquitously encoded serine threonine kinase. Previous studies have demonstrated that Mst1 has a tumor suppressor function in human breast cancer. Mst1 deletion or mutation is associated with tumorigenesis, whereas Mst1 overexpression leads to tumor cell apoptosis and decreases proliferation of tumor cells. Our previous study reported the tumor suppressive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(49 reference statements)
0
11
1
1
Order By: Relevance
“…In colorectal cancer, loss of cytoplasmic MST1 has been associated with higher T and/or N stage, higher tumor grade and poor prognosis [35]. Similarly, MST1 has been reported to be downregulated in breast cancer and proposed as a strong prognostic and predictive for disease-free survival [36,37]. Although we did not find a correlation between cytoplasmic expression and clinicopathological features, the nuclear expression of MST1 was significantly associated with pT stage and progression in our GBC cohort.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In colorectal cancer, loss of cytoplasmic MST1 has been associated with higher T and/or N stage, higher tumor grade and poor prognosis [35]. Similarly, MST1 has been reported to be downregulated in breast cancer and proposed as a strong prognostic and predictive for disease-free survival [36,37]. Although we did not find a correlation between cytoplasmic expression and clinicopathological features, the nuclear expression of MST1 was significantly associated with pT stage and progression in our GBC cohort.…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, the immunohistochemical evaluation of MST1 expression confirmed a diminished expression in GBC compared with CC. The anticancer effects of MST1 have been reported for numerous types of cancer, including colorectal [34,35], breast [10,36,37] and lung cancers [38]. It should be noted that cytoplasmic expression of MST1 in cancer cells has been related with its function as a protective molecule acting in the canonical Hippo signaling pathway, through the inhibition of oncogenic YAP/TAZ [33].…”
Section: Discussionmentioning
confidence: 99%
“… 41 protein 110 0.027 0.03 low 10% of SEP as cutoff breast cancer Lin X-Y et al . 42 protein 98 0.010 0.002 low detection on plasma by ELISA, average as cutoff colorectal cancer Yu J et al . 43 mRNA 46 0.0008 NA low microarray, ROC curve to set the cutoff colorectal cancer Minoo P et al .…”
Section: Resultsmentioning
confidence: 99%
“…Kinase signaling is a powerful and central cellular mechanism that mediates signal transduction events and is involved in a wide range of nearly all cellular processes including, but not limited to, the control of cell cycle progression, transcriptional regulation, cell transformation, proliferation, differentiation, and apoptosis. Given its central role in cellular function, aberrant regulation of kinase signaling can profoundly affect homeostasis and has been found to be involved in many disease states including insulin resistance [ 3 , 4 ], autoimmunity [ 5 , 6 ], viral infection [ 7 , 8 ], and oncogenesis [ 9 , 10 ]. Hence, assessing the kinome can provide insight into complex pathological processes across a wide array of diseases and has also been a well-studied target for therapeutics.…”
Section: Introductionmentioning
confidence: 99%